(untitled) (Itinera, 2022)
Since Virtual Reality (VR) is characterised by the absence of the frame, the VR user has the impression of being immersed into the image, thus overcoming the distinction between spectacle and spectator. Therefore, the user becomes herself part of the work of art, exposing the limits of the Cartesian dualisms dominating the Western thought and raising critical questions about traditional aesthetic categories. Hence, my paper aims at pondering on the ontological status of the VR user. In opposition to Simon Penny’s argument, which proposes that VR fragments the viewer into a physical body versus a virtual one, my research goal is to clarify that the participant’s physical body and virtual body are inseparable and firmly intertwined. In order to do so, I analyse the VR documentary Send me Home (Evanisko, 2019). The point of departure is the acknowledgment that the VR user is invisible both to herself and to the other characters with whom she shares the virtual space. Following Jacques Derrida’s Specters of Marx, I argue that this invisibility reveals the ontological status of the VR participant as a specter. However, my goal is to show that the spectrality of the user is not in contradiction with her carnality: on the contrary, even when one tries to bracket the body, the body remains vigilant, interpreting the world through its flesh. To conclude, then, I argue that the body is the condition of possibility for the user to feel immersed into the virtual world, and that, contrary to the fragmentation argument, physical body and virtual body cannot be thought as separate.